2020
DOI: 10.1186/s12889-020-08908-x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ perception of dietary behaviour in a public school in Chile: a focus groups study

Abstract: Background: The objective of this study was to assess dietary behavior among sixth-to eighth-grade students to inform the delivery and content of nutrition education. Methods: This was a qualitative study through focus groups. Subjects were 57 adolescents 10-14 years old, 30 males and 27 females distributed in six groups. To compare group responses, transcriptions were coded using the original question guide. The information was analyzed using the content analysis technique. Results: The main findings showed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Although numerous studies have shown that nutrition knowledge often does not translate into good dietary habits among adolescents, numerous recent intervention reports and reviews have shown improved dietary practices as a result of improvements in nutrition knowledge in this age group [ 20 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Nutrition education has been incorporated into the curricula of primary and secondary schools in Nigeria; however, recent research has shown poor levels of nutrition knowledge in public secondary schools in the country [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have shown that nutrition knowledge often does not translate into good dietary habits among adolescents, numerous recent intervention reports and reviews have shown improved dietary practices as a result of improvements in nutrition knowledge in this age group [ 20 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Nutrition education has been incorporated into the curricula of primary and secondary schools in Nigeria; however, recent research has shown poor levels of nutrition knowledge in public secondary schools in the country [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early adolescence would seem an ideal age for such programs [8,9]. During adolescence, the individual becomes more independent with respect to many matters including lifestyle choices [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Food consumption patterns have shifted to diets that are high in fat and insufficient in fruits and vegetables [ 6 ], and these habits can be possibly maintained into adulthood [ 9 ]. Since adolescence is a stage where individuals begin to make their own eating decisions, this provides a critical opportunity for introducing interventions that can influence attitudes toward healthy eating [ 3 , 14 ].…”
Section: Introductionmentioning
confidence: 99%